Case report: Envafolimab causes local skin necrosis - Liu, Jing Jing; Xu, Xiao Ya; Han, Huan; Wang, Tong; Zhang, Wei; Cui, Jing; Semenov, Maksim (Frontiers in Immunology, 2024)
Envafolimab is a China domestic innovative fusion of a humanized single-domain programmed death ligand (PD-L1) antibody (dAb) and human immunoglobulin IgG1 crystalline fragment (Fc) developed for subcutaneous injections and granted conditional market authorization by China National Medical Product Administration (NMPA) in December 2021. Envafolimab is used for treatment of adult patients with previously-treated microsatellite instability-high (MSI-H) or deficient MisMatch Repair (dMMR) advanced solid tumors, including patients with advanced colorectal cancer disease progression after previously administered Fluorouracil, Oxaliplatin, and Irinotecan, as well as other patients with advanced solid tumors who experienced disease progression after receiving standard treatment and have no other alternative treatment options. However, the small sample size of previous clinical trialslack of post marketing clinical trial data requires to conduct more clinical studies on the safety and efficacy of Envafolimab in order to provide scientific basis and references for future therapeutic applications. In this paper, we report a case of severe skin necrosis and bleeding in the area of injection after subcutaneous administration of Envafolimab in a patient diagnosed with hepatocellular carcinoma. We discuss issue that must be considered before administration of PD-L1 inhibitor subcutaneously that may induces immune mechanisms leading to the skin necrosis in the area of injection.